Pelaksanaan Program Communication and Relation Pertamina Refinery Unit II Dumai - Triono, Al Wahyu; Riauan, Muhd Ar. Imam (The Journal of Communication Management and Organization, 2022)
Abstract This study aims to determine the Communication Strategy of the Pertamina Refinery Unit II Dumai Communication and Relations Program. The selection of informants used a purposive technique that was deemed competent to explain the research objectives. Analysis of the data used in this study is a qualitative analysis in the form of verbal reports naturally. The results of the study show that the communication strategy carried out by PT. Pertamina RU II Dumai in the communication relation program activity begins with getting to know the audience, compiling messages, determining information delivery methods, selecting appropriate and effective media and determining communicators who have credibility and attractiveness in the message delivery process. Communication barriers that occur in the form of internal barriers in the form of changes in position, human resources and abilities that are not uniform.